"سياسة التشغيل في الجزائر : دراسة تقويمية لجهاز أونساج " - حاجي, مصباح (جامعة الوادي university el-oued)
"ملخص : لطالما بحثت الحكومات الجزائرية المتعاقبة، على حل لامتصاص الطلب المتزايد على التشغيل وقامت بوضع سياسات تشغيل مختلفة ، حيث شرعت في مجموعة من الإصلاحات الاقتصادية التي تهدف إلى تحسين مناخ الاستثمار و تشجيع القطاع الخاص، فسياسات التشغيل في الجزائر خلال السنوات الأخيرة أصبحت ترتكز على مجموعة من الأبعاد الاقتصادية و الاجتماعية و التنظيمية و الهيكلية الأمر الذي يجعلها تعتمد في تحقيق هذه الأهداف على مجموعة من الآليات و البرامج و المخططات. و من بين هذه الآليات نجد إستراتيجية القرض المصغر التي تعتبر برنامجا لمحاربة الهشاشة و الأوضاع المتردية داخل الطبقات الاجتماعية و تحسين مستواها المعيشي وهو موجه للأشخاص العاطلين عن العمل و يسمح للفئات المحرومة في المجتمع لخلق نشاطهم الخاص و إنشاء مؤسساتهم و مشاريعهم المصغرة ، و لهذا الغرض قامت الدولة الجزائرية بإنشاء الهياكل القادرة على تجسيد سياسة القرض المصغر و منها الوكالة الوطنية لدعم تشغيل الشباب "" أونساج "" و التي خصصتها الدولة لترقية و نشر الفكر المقاولاتي و تشكل أحد القنوات الموجهة لامتصاص ظاهرة"summary : Successive Algerian governments have always searched for a solution to absorb the increasing demand for employment and have developed different employment policies. They have embarked on a set of economic reforms aimed at improving the investment climate and encouraging the private sector. Employment policies in Algeria in recent years have become based on a set of dimensions Economic, social, organizational and structural, which makes it depend in achieving these goals on a set of mechanisms, programs and schemes. Among these mechanisms, we find the microcredit strategy, which is considered a program to combat vulnerability and deteriorating conditions within social classes and improve their standard of living. The Algerian state establishes structures capable of embodying the policy of microcredit, including the National Agency for Youth Employment Support “ONSAJ”, which was designated by the state to promote and disseminate entrepreneurial thought and constitutes one of the channels directed to absorb the phenomenon of unemployment and is the subject of the .
م.س.ع.21
Keywords: "الكلمات المفتاحية : سياسة التشغيل، الجزائر، جهاز اونساج ، البطالة، مناخ الاستثمار . "; "key words : Employment policy, Algeria, Onsage, unemployment, investment climate. "